Does Prefrontal Glutamate Index Cognitive Changes in Parkinson’s Disease? - Buard, Isabelle; Lopez-Esquibel, Natalie; Carey, Finnuella J.; Brown, Mark S.; Medina, Luis D.; Kronberg, Eugene; Martin, Christine S.; Rogers, Sarah; Holden, Samantha K.; Greher, Michael R.; Kluger, Benzi M. (Frontiers in Human Neuroscience, 2022)
Introduction Cognitive impairment is a highly prevalent non-motor feature of Parkinson’s disease (PD). A better understanding of the underlying pathophysiology may help in identifying therapeutic targets to prevent or treat dementia. This study sought to identify metabolic alterations in the prefrontal cortex (PFC), a key region for cognitive functioning that has been implicated in cognitive dysfunction in PD. Methods Proton Magnetic Resonance Spectroscopy was used to investigate metabolic changes in the PFC of a cohort of cognitively normal individuals without PD (CTL), as well as PD participants with either normal cognition (PD-NC), mild cognitive impairment (PD-MCI), or dementia (PDD). Ratios to Creatine (Cre) resonance were obtained for glutamate (Glu), glutamine and glutamate combined (Glx), N-acetylaspartate (NAA), myoinositol (mI), and total choline (Cho), and correlated with cognitive scores across multiple domains (executive function, learning and memory, language, attention, visuospatial function, and global cognition) administered to the PD participants only. Results When individuals retain cognitive capabilities, the presence of Parkinson’s disease does not create metabolic disturbances in the PFC. However, when cognitive symptoms are present, PFC Glu/Cre ratios decrease with significant differences between the PD-NC and PPD groups. In addition, Glu/Cre ratios and memory scores were marginally associated, not after Bonferroni correction. Conclusion These preliminary findings indicate that fluctuations in prefrontal glutamate may constitute a biomarker for the progression of cognitive impairments in PD. We caution for larger MRS investigations of carefully defined PD groups.